1998
DOI: 10.1038/32831
|View full text |Cite
|
Sign up to set email alerts
|

The complete genome of the hyperthermophilic bacterium Aquifex aeolicus

Abstract: Aquifex aeolicus was one of the earliest diverging, and is one of the most thermophilic, bacteria known. It can grow on hydrogen, oxygen, carbon dioxide, and mineral salts. The complex metabolic machinery needed for A. aeolicus to function as a chemolithoautotroph (an organism which uses an inorganic carbon source for biosynthesis and an inorganic chemical energy source) is encoded within a genome that is only one-third the size of the E. coli genome. Metabolic flexibility seems to be reduced as a result of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
735
3

Year Published

1998
1998
2006
2006

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 1,049 publications
(760 citation statements)
references
References 46 publications
19
735
3
Order By: Relevance
“…Sketched phylogenetic tree, according to the present knowledge (Woese et al+, 1990;Pace, 1997), showing distribution of the tRNA Sec secondary structure models+ The tRNA Sec secondary structure of the Archae M. jannaschii (sequence from Bult et al+, 1996) folds into the 9/4 model+ Dotted line represents a putative U-A base pair+ The tRNA Sec secondary structure of the hyperthermophilic bacterium A. aeolicus (sequence from Deckert et al+, 1998) folds into the 8/5 model, as do the other bacterial tRNAs Sec + An alternate 2D structure can be proposed for the D-stem with a C+C pairing+ The folding is 8/5 in bacteria (E. coli and A. aeolicus), 9/4 in Archaea (M. jannaschii ) and Eukarya (X. laevis)+ The M. jannaschii tRNA Sec sequence was extracted from the TIGR mjdatabase (positions 111766-111855)+ The A. aeolicus tRNA Sec sequence was found at NCBI, accession number AE000720 (positions 8711-8809)+ The E. coli and X. laevis tRNAs Sec sequences were from Tormay et al+ (1994) and Sturchler et al+ (1993), respectively+ D+ It is frequently observed that N1-As (here N1-A63) react rapidly with DMS, even when base paired with a U, sometimes leading to the wrong interpretation that an A could be single stranded+ This reactivity is very likely due to the small size of the reagent and breathing of the helix, providing enough transient accessibility of the N1-A for the chemical to react+ However, in the gel provided in Figure 2A, it is obvious that N1-A63 is protected under native conditions, thus base paired to U51+…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sketched phylogenetic tree, according to the present knowledge (Woese et al+, 1990;Pace, 1997), showing distribution of the tRNA Sec secondary structure models+ The tRNA Sec secondary structure of the Archae M. jannaschii (sequence from Bult et al+, 1996) folds into the 9/4 model+ Dotted line represents a putative U-A base pair+ The tRNA Sec secondary structure of the hyperthermophilic bacterium A. aeolicus (sequence from Deckert et al+, 1998) folds into the 8/5 model, as do the other bacterial tRNAs Sec + An alternate 2D structure can be proposed for the D-stem with a C+C pairing+ The folding is 8/5 in bacteria (E. coli and A. aeolicus), 9/4 in Archaea (M. jannaschii ) and Eukarya (X. laevis)+ The M. jannaschii tRNA Sec sequence was extracted from the TIGR mjdatabase (positions 111766-111855)+ The A. aeolicus tRNA Sec sequence was found at NCBI, accession number AE000720 (positions 8711-8809)+ The E. coli and X. laevis tRNAs Sec sequences were from Tormay et al+ (1994) and Sturchler et al+ (1993), respectively+ D+ It is frequently observed that N1-As (here N1-A63) react rapidly with DMS, even when base paired with a U, sometimes leading to the wrong interpretation that an A could be single stranded+ This reactivity is very likely due to the small size of the reagent and breathing of the helix, providing enough transient accessibility of the N1-A for the chemical to react+ However, in the gel provided in Figure 2A, it is obvious that N1-A63 is protected under native conditions, thus base paired to U51+…”
Section: Discussionmentioning
confidence: 99%
“…The second reason is supplied by evolutionary considerations+ The recent publication of the complete genome sequence of the hyperthermophilic bacterium Aquifex aeolicus (Deckert et al+, 1998) allowed us to fold the tRNA Sec sequence into the 8/5 secondary structure model as for the other bacterial tRNAs Sec (Fig+ 3)+ Several pieces of evidence point to the conclusion that the Archae and Eukarya share a common evolutionary trajectory independent of the lineage of bacteria (Woese et al+, 1990;Bult et al+, 1996; Pace, 1997)+ Also, the kinship degree between the bacterium A. aeolicus and the Archae M. jannaschii is far from being close (reviewed in Pennisi, 1998)+ Thus, the congruence of the 8/5 versus 9/4 tRNA Sec classification with the bacterial versus archaeal/eukaryal phylogenetic kingdom classification provides strong evidence for the 9/4 tRNA Sec structure+ Indeed, a 7/5 structure model for eukaryotes would lead to three different secondary structure models for the three different kingdoms instead of only two (Fig+ 3)+ Therefore, the 8/5 and 9/4 tRNA Sec classification that we posited is relevant, thus providing additional evidence for the merits of the archaeal tRNA Sec argument+…”
Section: Chemical Probingmentioning
confidence: 99%
“…Table 1 shows the subunit composition of our preparation. Interestingly, subunit b is encoded by two different genes [24] giving rise to two different b subunits, b 1 and b 2 . Both b 1 and b 2 could be detected in our A. aeolicus F 1 F 0 ATP synthase preparation by MALDI-MS through peptide mass fingerprinting or through MS/MS.…”
Section: Purification Of F 1 F 0 Atp Synthasementioning
confidence: 99%
“…aeolicus is such a hyperthermophilic eubacterium. Its genome has been sequenced [24]. We have previously used this organism to purify a highly stable and active NADH ubiquinone oxidoreductase -(complex I of the respiratory chain) [25].…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of phylogenetic analysis of the smallsubunit rRNA (16S rRNA) gene sequences, the Aquificales are the deepest lineage within the domain Bacteria (Burggraf et al, 1992 ;Pitulle et al, 1994). However, the recent genome sequence of Aquifex aeolicus (Deckert et al, 1998) and RNA polymerase sequence comparisons (Klenk et al, 1999) do not fully support the deeply rooted position of this order. Within the Aquificales, the Aquifex-CalderobacteriumHydrogenobacter-Thermocrinis lineage forms a separate clade from the environmental sequences obtained from thermal springs in Yellowstone (Reysenbach et al, 2000b), Japan (Yamamoto et al, 1998) and Iceland (Skirnisdottir et al, 2000).…”
Section: Introductionmentioning
confidence: 99%